Toward a Shared Future: Why a Federation is the Only Viable Solution to the Israeli-Palestinian Conflict - Galiñanes, Manuel; Klinkers, Leo (Advances in Social Sciences Research Journal, 2025)
This article argues that sustained external involvement—especially by the United States—has often undermined peace efforts through geopolitical bias and inconsistent diplomacy. Regional actors, too, have failed to maintain a unified stance on Palestinian self-determination, as demonstrated by shifting alliances and the sidelining of the Palestinian issue in agreements like the Abraham Accords. In light of these failures, a recalibrated regional approach rooted in justice and human rights is essential. The international community must shift toward mediation frameworks grounded in international law, ensuring symmetrical recognition of Israeli and Palestinian rights, and empowering local civil society—particularly on the Palestinian side. The European Union, given its relative neutrality and economic influence, is well-positioned to facilitate this shift. Most critically, the peace process must undergo structural transformation: instead of persisting with failed bilateral talks, a multilateral, inclusive framework should be adopted, involving regional and neutral international actors alongside representatives from both communities. This includes seriously considering a federal model that enables shared sovereignty, mutual recognition, and lasting security. Only through such a comprehensive rethinking can a just and enduring peace be achieved—one that halts the cycle of violence and contributes to regional and global stability.